Effects of Trade Openness, Investment and Population on the Economic Growth: A Case Study of Syria - Mohsen, Adel Shakeeb; Chua, Soo Y. (Faculty of Economic Sciences, Hyperion University, Bucharest, Romania, 2015)
This study attempts to investigate the role of trade openness, investment and population in the Syrian economy over the period 1980-2010. The cointegration test indicates that GDP is positively and significantly related to the trade openness, investment and population. The Granger causality test indicates bidirectional short-run causality relationships between trade openness, investment, population and GDP. There are also bidirectional long-run causality relationships between investment, population and GDP, and unidirectional long-run causality relationship running from trade openness to GDP. The study result indicates that population has the biggest effect on the GDP, thus we suggest improving the quality of the human capital in the country, as well as improving the investment and opening up the Syrian economy to foreign trade.